O20 Cai patients alter jump landing biomechanics differently than controls while wearing stroboscopic eyewear. (17th September 2017) - Wikstrom, EA; Rhodes, E; Franz, JR; Mihalik, JP
Abstract : Study Design: Repeated Measures. Objectives: To determine if CAI patients respond differently than controls during a jump landing task when visual information is reduced by using stroboscopic eyewear. Background: CAI patients have an increased reliance on visual information during feedback static postural control tasks. CAI patients also have known feedforward neuromuscular alterations and altered jump landing biomechanics relative to controls. However, the influence of visual information when planning a jump landing task in CAI patients relative to controls remains unknown. Methods and Measures: Ten subjects (five controls; five with self-reported CAI) participated. CAI was defined in accordance with the International Ankle Consortium guidelines. Three Landing Error Scoring System (LESS) jump landings were completed under three visual conditions: eyes open (EO), eyes open with low stroboscopic interference (EOLS), and eyes open with high stroboscopic interference (EOHS). The LESS requires participants to jump down from a 30 cm high box placed 50% of the participant's height away from the landing zone. Peak plantar flexion and knee flexion were assessed by a PhysiMax movement assessment system (Bronx, NY). For this preliminary investigation, a liberal alpha level of 0.10 was used to determine statistical significance. Results: CAI participants reduced knee flexion as visual information was reduced (EO: 87.69±10.95°; EOLS: 81.46±11.78°; EOHS: 80.70±17.08°), but control participants did not follow this trend (EO: 79.33±8.30°; EOLS: 82.40±6.75°; EOHS: 80.7±17.08°; interaction p=0.095). No interaction was noted for plantar flexion (p=0.39) despite control participants reducing plantar flexion as visual information was reduced (EO: 4.38±3.00°; EOLS: 2.50±2.76°; EOHS: 2.66±3.62°) while CAI patients did not (EO: 5.99±0.86°; EOLS: 5.44±2.30°; EOHS: 6.56±1.36°). Conclusions: Reducing visual information by using stroboscopic interference influences how CAI patients complete a jump landing differently from controls. Controls appear to be effective at dynamically reweight to other sources of sensory information when planning and executing a jump landing.